2009
DOI: 10.1111/j.1447-0594.2009.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment of elderly highlanders in Qinghai, China I: Activities of daily living, quality of life and metabolic syndrome

Abstract: Prevalence of metabolic syndrome in elderly highlanders in Qinghai was still not high, however, we should pay attention to its tendency related with socialglobalism in the near future. Further investigation on physiological adaptability to hypoxic environment and human ageing phenomena in a global context may open a new research frontier for ageing science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
(40 reference statements)
3
14
1
Order By: Relevance
“…However, in the present study, the association between OC and adiponectin was not identified. Consistent with other studies , we found an inverse association between OC and leptin. Ducy et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the present study, the association between OC and adiponectin was not identified. Consistent with other studies , we found an inverse association between OC and leptin. Ducy et al .…”
Section: Discussionsupporting
confidence: 93%
“…Lu et al . found that serum OC was not associated with glucose in nondiabetic women . Abseyi et al .…”
Section: Discussionmentioning
confidence: 95%
“…Such inflexibility and fatty acid oxidation capacities [39, 40] are both implicated in the pathogenesis of type 2 diabetes mellitus. Tibetan highlanders have a relatively low prevalence of diabetes [41], but the diet is also relatively low-calorie [42] and high altitudes are associated with lower body weights among Tibetans [43]. As populations move to lower altitudes and encounter a more industrialized lifestyle and higher calorie diets, however, the metabolic adaptations to altitude could have health implications.…”
Section: Resultsmentioning
confidence: 99%
“…However, globalization has now reached the Himalayan highlands. Residents, even of the highlands, have also experienced an increase in life expectancy, but at the same time a higher rate of lifestyle‐related diseases has been identified 68–72 . The physiological adaptations to the low‐oxygen environment were caused by gradual genetic changes that took place over tens of thousands of years.…”
Section: Expansion Of Field Medicine To Atypical Global Environments mentioning
confidence: 99%